Recommended Reads: Decentering Whiteness in Children's Literature - David Valente (CLELEjournal, 2020)
Bryon, Nathan & Adeola, Dapo (2019) Look Up! Mian, Zanib & Mafaridk, Nasaya (2019) Planet Omar: Accidental Trouble Magnet Flowers, Ebony (2019) Hot Comb Thomas, Angie (2017) The Hate U Give (THUG)